Preparation of activated carbon from the decomposition products of coconut shell in basic medium with the presence of phenol and oxidizing bitumen's material from Hammam al-Alil - Mayada Ali (College of Education for Pure Sciences, 2012)
Abstract The study involve preparation of activated carbon from coconut shell hydrolyzed in basic medium, The water removed from hydrolyzed products and the residual materials were treated with constant amount of phenol in presence potassium hydroxide, then bitumen's material was added with different ratio's, The amount of reactants carbonated material and bitumen's material were verified using different ratio's to obtain a better result of iodine number adsorption and methylene blue pigment adsorption, Also observation the rule of base in structural formula damage with converted to activated carbon. The study showed that the reaction between oxidizing bitumen's, phenol products with decomposition material of coconut shell lead to formation of different types of activated carbons depend upon adsorption of Iodine and Methylene blue pigment and other factors.